ANALYSIS OF CONSUMER DIFFERENCES IN DECIDING TO CHOOSE RETAIL MIX IN CONVENIENCE STORE - Sri Nastiti Andharini; Marsudi Marsudi (Manajemen Bisnis, 2019)
The purpose of this study was to analyze and test the differences in consumers in choosing retail mix at convenience stores at Giant Malang Olympic Garden and Hypermart Malang Town Square. The research conducted was descriptive research, with the technique of data collection used was a questionnaire. While the data analysis used is discriminant analysis.The results showed that there was a difference between consumers choosing retail mix at convenience stores at Giant Malang Olympic Garden and Hypermart Malang Town Square. What distinguishes consumers from choosing a retail mix at a convenience store at Giant Malang Olympic Garden and Hypermart Malang Town Square is offering various types of products, affordable prices, attractive discounts, providing a oduct catalog that makes it easier for consumers to choose products that will purchased, offering a bundling program (getting free other products that are usually packaged with the main product sold) on certain products, strategic locations (in the city center), always maintained conditions (neat, clean, and always paying attention interior design inside the store).